Study on the Performance and Hydration Mechanism of Hybrid Activation of Vanadium-Titanium Iron Ore Tailings - Xiaoping, Tian (International Journal of Integrated Engineering, 2025)
This paper investigates the activation of vanadium titanium iron ore tailings (VTIOT) to enhance their cementitious potential. Building upon previous studies, it explores two hybrid activation methods, thermal and chemical activation, to analyze how calcination temperature affects the physical and chemical properties of VTIOT and the performance of resulting cementitious materials, and how different activators affect the performance of VTIOT cementitious materials, and to analyze the mechanism of hydration. Through various analyses including TG-XRD, SEM, alkali leaching, mechanical testing, hydration heat analysis, and TGA, the hydration mechanism of VTIOT cementitious materials is examined. Results indicate minimal changes in micro-morphology and mineral phase of VTIOT calcined within a range of 550℃ to 950℃ for 2 hours. Moreover, mortars doped with 30% of VTIOT from different calcination temperatures exhibit comparable compressive strength and activity index to uncalcined VTIOT. Notably, a 0.2‰ dosage of Diethanolisopropanolamine (DEIPA) yields an 85% activity index, outperforming other dosages and activators. Additionally, DEIPA prolongs the induction period of hydration heat and increases the exothermic peak and hydration exotherm amount within 7 days compared to other activators. These findings shed light on the efficacy of hybrid activation methods and the influence of activators on the hydration kinetics of VTIOT cementitious materials.